Quantifying the evolution of early life numerical approaches to the evaluation of fossils and ancient ecosystems - Laflamme, Marc.; Schiffbauer, James D.; Dornbos, Stephen Q.; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
This volume provides a detailed description of a wide range of numerical, statistical or modeling techniques and novel instrumentation separated into individual chapters written by paleontologists with expertise in the given methodology. Each chapter outlines the strengths and limitations of specific numerical or technological approaches, and ultimately applies the chosen method to a real fossil dataset or sample type. A unifying theme throughout the book is the evaluation of fossils during the prologue and epilogue of one of the most exciting events in Earth History: the Cambrian radiation.
Electronic reproduction.
Keywords: Paleontology -- Precambrian; Fossils; Electronic books